Miniature rose alleviates inflammatory bowel disease in mice by modulating gut microbiota, inhibiting TLR4, enhancing tight junction proteins, and promoting metabolism - Wu, Jiaying; Mao, Xuwen (Frontiers in Microbiology, 2026)
IntroductionInflammatory bowel disease (IBD) is a chronic, relapsing inflammatory disorder of the gastrointestinal tract. Its pathogenesis is complex and not fully understood, so it remains incurable. Traditional Chinese medicine (TCM) attracts attention as a potential option. It offers multi-target actions. This study investigated the protective effects of an aqueous extract of Miniature Rose (MR), a medicinal plant from Xinjiang, in a dextran sulfate sodium (DSS)-induced murine model of IBD. We focused on gut microbiota, intestinal barrier integrity, and metabolic homeostasis.MethodsIBD was induced in mice by DSS, followed by intervention with different doses of aqueous MR extract. A multi-faceted approach incorporating 16S rRNA sequencing, non-targeted metabolomics, immunohistochemistry, and ELISA was used to evaluate the effects of MR on gut microbiota composition, fecal metabolic profiles, intestinal barrier protein expression, and the expression of the inflammatory proteins TLR4 and TLR9.ResultsTreatment with aqueous MR extract markedly alleviated DSS-induced colitis. MR improved intestinal barrier integrity by upregulating the tight junction proteins Occludin (OCC) and Zonula Occludens-1 (ZO-1), while concurrently downregulating TLR4 and TLR9. MR administration also markedly modulated the gut microbiota, increasing the relative abundance of beneficial genera (Bacteroides and Alloprevotella) and decreasing the abundance of the pathobiont Erysipelatoclostridium. In addition, MR mitigated the metabolic dysregulation observed in DSS-induced colitis.ConclusionMR ameliorates DSS-induced colitis through a multifaceted mechanism that involves coordinated regulation of the gut microbiota, restoration of the intestinal barrier, inhibition of inflammatory protein expression, and correction of metabolic dysregulation. These findings highlight the potential of MR as a multi-target therapeutic candidate and provide an experimental basis for its further preclinical and clinical evaluation in IBD.